CITRA DIRI INDIVIDU DAN NEGOSIASI MUKA WARGA DENGAN BUDAYA KOLEKTIVISME DI NEGARA BERBUDAYA INDIVIDUALISME - Syarizka, Deandra; Nareswari, Kinanthi; Irwansyah, Irwansyah (Master of Communication Science Program, Universitas Diponegoro, 2021)
Most of the Indonesian citizens implement a collectivism culture considering that Indonesia is one of the countries that implement a collectivism culture according to Hofstede's Cultural Dimensions Theory. Indonesian citizens who migrate and live-in countries that implement individualism culture will feel the differences in their culture, which has the potential to produce intercultural communication conflicts. The Face Negotiation Theory that was initiated by Ting-Toomey explains that there are various approaches to resolving intercultural conflicts that exist. This research analyses the concept of self-construal and intercultural communication conflict management approaches used by two Indonesian citizens who are migrating in the United States and Australia through interviews and literature studies. The results of the study found the fact that the difference in self-construal concepts by each informant could produce the different approaches in managing conflict in communication between cultures, even though both informants were from countries with collectivism cultures.